Seroprevalence of viral and bacterial pathogens among malaria patients in an endemic area of southern Venezuela - David A. Forero-Peña; Fhabián S. Carrión-Nessi; Mary Lopez-Perez; Marisol Sandoval-de Mora; Iván D. Amaya; Ángel F. Gamardo; Melynar Chavero; Luisamy Figuera; María V. Marcano; Natasha A. Camejo-Ávila; Mariana Hidalgo; Cariagne J. Arenas; et al. (BMC, 2023)
Abstract Background Malaria remains a leading public health problem worldwide. Co-infections with other pathogens complicate its diagnosis and may modify the disease's clinical course and management. Similarities in malaria clinical presentation with other infections and overlapping endemicity result in underdiagnosis of co-infections and increased mortality. Thus, the aim of this study was to determine the seroprevalence of viral and bacterial pathogens among diagnosed malaria patients in malaria-endemic areas in Venezuela. Methods A cross-sectional study was conducted on malaria patients attending three reference medical centres in Ciudad Bolivar, Venezuela. Clinical evaluation and laboratory tests for dengue virus (DENV), chikungunya virus (CHIKV), viral hepatitis [hepatitis A virus (HAV), hepatitis B virus (HBV), and hepatitis C virus (HCV)], and leptospirosis (LEP) were performed by enzyme-linked immunosorbent assays. Previous exposure to these pathogens was defined by the presence of specific immunoglobulin (Ig) G, and co-infection or recent exposure (CoRE) was determined by the presence of specific IgM alone or IgM + IgG. Data analysis considered descriptive statistics. Parameter distribution was statistically evaluated using Kolmogorov-Smirnov test and the necessary comparison tests. Odds ratio (OR) for complications was determined according to CoRE presence with a 95% confidence interval (CI). Results A total of 161 malaria patients were studied, 66% infected with Plasmodium vivax, 27% with P. falciparum, and 7.5% harboured P. vivax/P. falciparum mixed infection. Previous exposure to DENV (60%) and CHIKV (25%) was frequent. CoRE was confirmed in 55 of the 161 malaria patients (34%) and were more frequent in P. falciparum (49%) than in P. vivax (29%) and mixed malaria patients (25%) (OR = 2.43, 95% CI: 1.39-4.25, P = 0.018). The most frequent CoRE was DENV (15%), followed by HAV (12%), HBV (6.2%), CHIKV (5.5%), and LEP (3.7%); HCV CoRE was absent. Complicated malaria was significantly more frequent in patients with CoRE (56%) than those without CoRE (36%; OR = 2.31, 95% CI: 1.18-4.92, P = 0.013). Conclusions We found high CoRE prevalence in malaria patients as determined by serology in the study region; cases were associated with a worse clinical outcome. Further prospective studies with samples from different infection sites and the use of molecular tools are needed to determine the clinical significance of these findings. Graphical abstract